(untitled) (Fiep Bulletin - online, 2012)
The Mental Training (TM) is a procedure used to assist in the physical training of athletes, where the mind through conditioning the athlete can improve factors related to the competitive situation, such as reduced anxiety, improved self-control and motivation. In addition, the TM with physical training can be an important ally to improve the physical and psychological capacities. The TM, developed into a sport that will not change the environment, may allow the athlete greater focus on learning the essential techniques for greater cognitive control of your body. The Indoor Cycling because it is a sport performed in stationary bikes can facilitate the use of TM. With the objective of this study was to analyze the influence of TM on amateur athletes through practice Indoor Cycling. The study lasted three months, three times weekly, lasting 50 minutes each. After signing the informed consent from volunteers, 10 athletes participated in the experiment. In one recent class was proposed a test related to TM in order to know if the athletes had learned to use some of the techniques of TM, such a test was carried out on the bike stationary indoor bike, analyzing the pedaling cycle in a minute, where was a stipulated charge and within a minute should do as many rounds were held in the same class four tests identical to that in which the strategies were modified, the first strategy without the TM and the other with the TM. According to the results obtained it can be concluded that the TM was shown to be an important and complementary to physical training, as the athletes had better performance with its use.